+0  
 
+1
23
1
avatar+1729 

#15 Help.

NotSoSmart  Feb 12, 2018
Sort: 

1+0 Answers

 #1
avatar+82944 
+1

√ [ 7x ] ( √x  - 7√7 )  =

 

(We are just using the distributive property here, like normal )

 

√ [7x] * √x    -    √ [7x] *  7√ 7  =

 

√ [ 7 * x^2 ]   -   7√ [  7x * 7 ]  =

 

x√ 7  -  7 √  [49 x ]   =

 

x √7  -  7 * 7√ x  =

 

x√7  -  49√x

 

 

cool cool cool

CPhill  Feb 12, 2018

13 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details